2021
DOI: 10.3390/app11135765
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Potential of a Novel Vitamin B2-Overproducing Lactobacillus plantarum Strain, HY7715, Isolated from Kimchi

Abstract: Vitamin B2, also known as riboflavin, is essential for maintaining human health. The purpose of this study was to isolate novel lactic acid bacteria that overproduce vitamin B2 and to validate their potential as probiotics. In this study, Lactobacillus plantarum HY7715 (HY7715) was selected among lactic acid bacteria isolated from Kimchi. HY7715 showed a very high riboflavin-producing ability compared to the control strain due to the high expression of ribA, ribB, ribC, ribH, and ribG genes. HY7715 produced 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Studies on the selection and effectiveness of probiotic strains with an excellent riboflavin-producing ability have been reported, and the production of riboflavin after intestinal settlement through probiotics has been reported to have a double effect on the basic functionality of probiotics [29,30]. In our previous studies, we demonstrated the vitamin B2 production ability and high survival rate of the L. plantarum HY7715 (HY7715) strain against gastric and bile acids, and the safety of the HY7715 strain was confirmed through Minimum Inhibitory Concentration (MIC) and hemolysis tests [31].…”
Section: Introductionmentioning
confidence: 87%
“…Studies on the selection and effectiveness of probiotic strains with an excellent riboflavin-producing ability have been reported, and the production of riboflavin after intestinal settlement through probiotics has been reported to have a double effect on the basic functionality of probiotics [29,30]. In our previous studies, we demonstrated the vitamin B2 production ability and high survival rate of the L. plantarum HY7715 (HY7715) strain against gastric and bile acids, and the safety of the HY7715 strain was confirmed through Minimum Inhibitory Concentration (MIC) and hemolysis tests [31].…”
Section: Introductionmentioning
confidence: 87%
“…In this study, we characterized the healthy human isolate L. reuteri AMBV339 with natural riboflavin production levels of 18.36 μg/ml in standard laboratory conditions. Based on the available literature, L. reuteri AMBV339 demonstrates the highest riboflavin production levels described for non-modified lactobacilli isolates in standard non-optimized growth conditions (MRS broth, 37°C, 24 h), which so far appear to be in the maximum range of 3–5 μg/ml ( 14 , 16 18 ). Although genetic modification of the riboflavin biosynthesis pathway in Lactococcus lactis NZ9000 resulted in overproduction up to 24 μg/ml of riboflavin ( 50 ), live genetically modified strains are currently not allowed to be used for food fortification in the European Union according to the opinion of the EFSA Panel on Genetically Modified Organisms ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study describing an L. reuteri strain with a spontaneous riboflavin-overproducing phenotype. Besides the well-reported investigation and applications of overproducing L. plantarum strains ( 16 , 18 , 52 56 ) only few other species of food-grade bacteria including L. lactis ( 50 ), Leuconostoc mesenteroides, Propionibacterium freudenreichii ( 43 ); Limosilactobacillus fermentum ( 57 ); Weissella cibaria , and Leuconostoc spp. ( 58 ) have been reported for the vitamin B2 bio-enrichment of fermented foods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations